Media Pembelajaran Flipbook Berbasis Masalah pada Muatan IPA untuk Siswa Kelas V Sekolah Dasar - Aryanti, Kadek Diva; Agung, Anak Agung Gede; Astawan, I Gede (Universitas Pendidikan Ganesha, 2025)
The lack of media variation used by teachers in the learning process has an impact on student learning outcomes which are still low. This study aims to determine the design, quality, and effectiveness of problem-based flipbook media on science content for fifth grade elementary school students. This study is a development research with the ADDIE development model. The subjects of this study were all fifth grade elementary school students totaling 29 students. The data analysis technique in this study was quantitative descriptive analysis and inferential statistical analysis. The research data were collected using a questionnaire sheet and multiple-choice test. The results of the study showed that the problem-based flipbook product is effectively applied to the content of science lessons, especially the material on eating and being eaten in a class V ecosystem in elementary schools. The implication of this study is that there needs to be support and commitment from the school to always apply media in the learning process.